Experimental Immigration Mediates Ecological Selection and Drift in Monarch Microbiome Assembly - Christopher P. Catano; James G. DuBose; Lydia Fuller‐Hall; Joselyne Chavez; Jacobus C. de Roode (Ecology Letters, 2025)
The distribution of biodiversity depends on processes operating across scales, yet multiscale paradigms have struggled to permeate host‐microbiome research. Instead, host‐microbiome research has focused on host selection and has struggled to explain the high variation in microbial composition across individuals. By integrating multi‐scale ecological theory with experimental manipulation of bacteria colonizing monarch butterfly caterpillars, we test the hypothesis that immigration from the regional species pool alters the importance of niche selection and drift in causing variation in gut bacterial communities across individuals and through ontogeny. Higher immigration increased the dominance of certain bacteria, causing greater convergence in bacterial composition across the caterpillar life stage. Conversely, limited immigration made colonization more stochastic, resulting in more unpredictable variability in bacterial composition across individuals. Our study reveals that immigration mediates the balance between host selection and drift, demonstrating that processes operating at scales beyond the individual are underappreciated but critical for structuring host‐microbiome symbioses.